GUIDELINES FOR THE RATIONAL USE OF BRONCHODILATORS IN CHILDREN UNDER 3 YEARS OF AGE - Usmonova Feruza Tokhirjonovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article presents a critical overview of the rational use of bronchodilators in children under three years of age. It addresses the pharmacological basis, clinical indications, administration methods, and safety considerations specific to this vulnerable age group. Drawing on international pediatric guidelines, the paper emphasizes evidence-based prescribing, individualized risk-benefit assessment, and the need to avoid overtreatment in cases of nonspecific wheezing. The aim is to provide a structured framework for optimizing respiratory care while minimizing adverse outcomes.